Economic burden of migraine in Latvia and Lithuania: direct and indirect costs - Ágnes Lublóy (BMC, 2019)
Abstract Background Migraine is a primary headache disorder which affects all aspects of life. The financial burden of migraine imposed on the society might be substantial. This study aims at estimating the economic cost of migraine in Latvia and Lithuania, including both direct and indirect costs. Direct costs encompass the costs of migraine-related health care resource utilization. Indirect costs are related to productivity loss, the potential or expected earnings lost due to migraine. Methods Direct cost is assessed by using the prevalence method, a widely used cost-of-illness approach. The prevalence rate of migraine and the migraine-related health care resource utilization are proxied from the literature, whereas unit cost of medical services and procedures are retrieved from national databases and providers. For estimating the indirect cost of migraine, we follow the human capital approach. We quantify three components of indirect costs: reduced labour force participation, absence from work and reduced productivity while at work. The number of unemployed migraineurs, days missed from work and days lost due to impairment while at work are drawn from the literature. Unemployment rate and average income in Latvia and Lithuania are then inserted to assess indirect costs. Results We find that the mean per-person total cost of migraine is €801 annually in Latvia, and €721 in Lithuania. In both countries around 30% of total cost is direct cost; cost related to a wide array of migraine-related medical services and interventions. The total cost of migraine is €112.26 million in Latvia, corresponding to 0.42% of Latvia's GDP. The total cost of migraine is €149.62 million in Lithuania, corresponding to 0.35% of Lithuania's GDP. In both countries two thirds of total cost is related to lost workdays due to absenteeism and presenteeism. Conclusions The financial burden of migraine imposed on the society is substantial in Latvia and Lithuania. Improvements in care for patients with migraine, such as easier access to structured headache assessment services, wider availability of various procedures and preventive medications would significantly increase direct costs. Nevertheless, this cost increase might be far outweighed by lower migraine-related productivity loss, especially as the prevalence of migraine is the highest in the most productive years of life.